Sharp drop in youth unemployment in Germany but regional differences remain - Karl Branke (DIW Economic Bulletin, 2013)
Youth unemployment in Germany has fallen to its lowest level since reunification. Between 2005 and 2012, unemployment among under 25 year olds has more than halved. By international standards, Germany is in an exceptionally strong position. Nowhere in Europe is youth unemployment lower. However, this is not so much due to structural improvements or positive labor market growth than to demographic change: the drop in youth unemployment is primarily a result of the declining number of young people. In other European countries, even qualified young people have a hard time gaining a foothold in the labor market, while in Germany it is predominantly young people with no formal vocational training who are unable to find a job despite the relatively positive economic situation. It also appears that there is insufficient mobility on the German labor market. On the one hand, there is an abundance of apprenticeships in some regions. On the other hand, an increasing regional concentration of youth unemployment is evident. Particularly in old industrial regions of western Germany and in eastern Germany, the unemployment rate for young people is well above the national average. However, it is precisely in these regions that the proportion of young people dropping out of vocational training or leaving school with no qualifications is particularly high. These young people run the risk of being permanently trapped in a precarious situation.
Keywords: J13; J60; J61; 330; youth unemployment in Germany